2011
DOI: 10.4149/av_2011_03_243
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Lyn kinase upregulates both canonical and non-canonical TLR-3 pathways in THP-1 monocytes exposed to human cytomegalovirus

Abstract: Summary. -Regulation of monocyte response to human cytomegalovirus (HCMV) occurs via activation of receptors that elicit innate antiviral effects and later T-cell responses. Our previous data (Yew et al.., 2010) demonstrated that human monocyte scavenger receptor A type 1 (SR-A1) are required for sensing of HCMV by endosomal toll-like receptors (TLRs)-3 and -9, which in turn induce critical pro-inflammatory cytokines. However, it remains unclear which subcellular molecules associated with SR-A1 lead to downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…It is well established that, among other innate receptors, TLR2, TLR4, and CD14 recognize HCMV virions (34,35), leading to downstream activation of NF-κB. Recognition of HCMV by monocytes has also been shown to occur via an alternative pathway involving scavenger receptor A1, endosomal TLR-3, and the adaptor protein TRIF, resulting in IL-12 and TNF-α transcription (36). In our cocultures, a small subset of CD14 + cells was the only cell population within PBMCs displaying detectable IL-12 production in an early time window of 24 to 36 hours after infection of cocultured MRC-5 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that, among other innate receptors, TLR2, TLR4, and CD14 recognize HCMV virions (34,35), leading to downstream activation of NF-κB. Recognition of HCMV by monocytes has also been shown to occur via an alternative pathway involving scavenger receptor A1, endosomal TLR-3, and the adaptor protein TRIF, resulting in IL-12 and TNF-α transcription (36). In our cocultures, a small subset of CD14 + cells was the only cell population within PBMCs displaying detectable IL-12 production in an early time window of 24 to 36 hours after infection of cocultured MRC-5 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies with Mouse cytomegalovirus (MCMV) reported that TLR2, TLR3, TLR7 and TLR9 are involved in the viral sensing of and initiation of innate immunity against MCMV (Bozza et al, 2006;Szomolanyi-Tsuda et al, 2006;Crane et al, 2012;Traub et al, 2012). Similarly, in the case of HCMV infection, a significant role was reported for the same four TLRs (Varani et al, 2007;Iversen et al, 2009;Yew et al, 2010;Yew & Harrison, 2011). Studies showed that TLR alterations at the maternal-fetal interface are involved in innate immunity during gestation, as also observed in the case of HCMV (Chaudhuri et al, 2009) and bacterial infections (Holmlund et al, 2002;Forster-Waldl et al, 2005;Zariffard et al, 2005;Sadeghi et al, 2007;Rose et al, 2011), as well as in the pathogenesis of adverse pregnancy outcomes Ilievski et al, 2007;Ilievski & Hirsch, 2010;Sado et al, 2011;Wujcicka et al, 2013).…”
Section: Tlrs Contribute To Immune Response Against Hcmvmentioning
confidence: 72%
“…In addition, studies with neutralizing antibodies and morpholino antisense oligonucleotides showed that transcription of tumor necrosis factor alpha (TNF-a) and interleukin 12 (IL-12) observed within 10 min was likely TLR2-dependent, whereas TLR3-mediated IFN-b and TLR9-mediated TNF-a expression appearing within 1 h was dependent on SR-A1 (Yew et al, 2010). Another study showed that SR-A1-dependent induction of TLR3/9 signaling pathway was regulated via Lyn kinase, physically and functionally associated with SR-A1 (Yew & Harrison, 2011). Another study showed that SR-A1-dependent induction of TLR3/9 signaling pathway was regulated via Lyn kinase, physically and functionally associated with SR-A1 (Yew & Harrison, 2011).…”
Section: Tlrs Contribute To Immune Response Against Hcmvmentioning
confidence: 99%
“…This is evidence of activation of multiple TLR pathways in a single cell. This group later showed that blocking Lyn kinase, which is associated with SR-A1, leads to inhibition of TLR9 signaling and shifts the response to a primarily TLR3 driven IFN-β response but also a non-canonical TLR3 driven NF-κB response (Yew and Harrison, 2011). …”
Section: β-Herpesvirusesmentioning
confidence: 99%